Temporal Hyporheic Zone Response to Water Table Fluctuations. Issue 2 (19th June 2015) - Malzone, Jonathan M.; Anseeuw, Sierra K.; Lowry, Christopher S.; Allen‐King, Richelle
Abstract: Expansion and contraction of the hyporheic zone due to temporal hydrologic changes between stream and riparian aquifer influence the biogeochemical cycling capacity of streams. Theoretical studies have quantified the control of groundwater discharge on the depth of the hyporheic zone; however, observations of temporal groundwater controls are limited. In this study, we develop the concept of groundwater‐dominated differential hyporheic zone expansion to explain the temporal control of groundwater discharge on the hyporheic zone in a third‐order stream reach flowing through glacially derived terrain typical of the Great Lakes region. We define groundwater‐dominated differential expansion of the hyporheic zone as: differing rates and magnitudes of hyporheic zone expansion in response to seasonal vs. storm‐related water table fluctuation. Specific conductance and vertical hydraulic gradient measurements were used to map changes in the hyporheic zone during seasonal water table decline and storm events. Planar and riffle beds were monitored in order to distinguish the cause of increasing hyporheic zone depth. Planar bed seasonal expansion of the hyporheic zone was of a greater magnitude and longer in duration (weeks to months) than storm event expansion (hours to days). In contrast, the hyporheic zone beneath the riffle bed exhibited minimal expansion in response to seasonal groundwater decline compared to storm related expansion. Results indicated that fluctuation in the riparian water table controlled seasonal expansion of the hyporheic zone along the planar bed. This groundwater induced hyporheic zone expansion could increase the potential for biogeochemical cycling and natural attenuation.